SOSIALISASI PEMERIKSAAN BACTERIAL VAGINOSIS DAN URINE LENGKAP PADA IBU PKK DI DESA SUMBERSONO MOJOKERTO - Anggraini, Rahayu; Firdaus; Handayani; Fenita Tanjung Maharani; Ainania Aura Sabriena Putri; Tryana Nur Rahmadani; Hellen Thesta Fanessia (Jurnal Pengabdian Masyarakat (Jupemas), 2025)
Women's reproductive health, especially among those of reproductive age, is highly susceptible to disorders such as urinary tract infections (UTIs) and bacterial vaginosis (BV). A lack of understanding about risk factors, symptoms, and preventive measures has led to a high incidence of undetected infections. Therefore, education and early detection are crucial steps to reduce the risk of long-term complications. This activity aims to enhance the knowledge of PKK mothers regarding the dangers of UTI and BV, as well as the importance of early detection through health education and simple examinations. The activity was conducted in Sumbersari Village, Sumbersono Village, Mojokerto District, involving 19 female participants. The implementation methods included pre-test and post-test questionnaires, educational material delivery using LCD (Liquid Crystal Display) media, posters, and complete urine examinations and vaginal swabs (Bacterial Vaginosis/BV) with Gram staining. The results showed an increase in participants' understanding post-education from 40-50% to 70-80%. Complete urine tests identified that 50% of participants had uric acid crystals, 30% had cloudy urine, and 10% were positive for BV based on the presence of clue cells. The conclusion of this activity indicates that structured education combined with laboratory examinations can enhance knowledge and awareness of the importance of reproductive health, thereby enabling early prevention through proper hygiene of reproductive organs and regular BV and UL examinations at the community level.